2021
DOI: 10.3389/fphar.2021.797110
|View full text |Cite
|
Sign up to set email alerts
|

Pyroptosis: A New Insight Into Eye Disease Therapy

Abstract: Pyroptosis is a lytic form of programmed cell death mediated by gasdermins (GSDMs) with pore-forming activity in response to certain exogenous and endogenous stimuli. The inflammasomes are intracellular multiprotein complexes consisting of pattern recognition receptors, an adaptor protein ASC (apoptosis speck-like protein), and caspase-1 and cause autocatalytic activation of caspase-1, which cleaves gasdermin D (GSDMD), inducing pyroptosis accompanied by cytokine release. In recent years, the pathogenic roles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 174 publications
0
19
0
Order By: Relevance
“…That may be a deep underlying mechanism for the promoted transduction of NLRP3/Caspase-1/GSDMD signaling axis, which consequent a pyroptotic death of corneal epithelium in BAC-DED. Though several reports have indicated the role of pyroptosis in the development of DED, 14 , 63 , 64 the BAC-induced corneal epithelium pyroptosis has not been reported before. The present study provided new insights into the adverse effects of BAC, which can serve as a new target for the protection of corneal epithelium when applying BAC as a preservative in eye drops.…”
Section: Discussionmentioning
confidence: 94%
“…That may be a deep underlying mechanism for the promoted transduction of NLRP3/Caspase-1/GSDMD signaling axis, which consequent a pyroptotic death of corneal epithelium in BAC-DED. Though several reports have indicated the role of pyroptosis in the development of DED, 14 , 63 , 64 the BAC-induced corneal epithelium pyroptosis has not been reported before. The present study provided new insights into the adverse effects of BAC, which can serve as a new target for the protection of corneal epithelium when applying BAC as a preservative in eye drops.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, emerging studies have shown that in lens/LECs, aging and oxidative stress can induce various types of program cell death, such as apoptosis, pyroptosis, and ferroptosis [6,51,131,132]. It has been established that these program cell deaths are linked to the onset of cataractogenesis [133][134][135][136]. It is worth mentioning that in vitro experiments conducted with Hyd at concentrations of 20 to 50 µM appear to be pharmacologically and physiologically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…The thioredoxin‐interacting protein can be dissociated by excessive ROS and binds to the inflammasome assembly followed by the activation of NLRP3 inflammasome (Tang et al, 2019). The upregulation of NLRP3 transcription promotes recruitment of the adapter ASC and, in turn, recruiting procaspase 1, which plays a crucial role in pyroptosis and multiple eye diseases (Shao et al, 2016; Y. Zhang et al, 2021). ASC serves as one of the platforms for the proteolytic maturation of caspase‐1, and caspase 1 induces ASC‐mediated necrosis (Motani et al, 2011).…”
Section: Discussionmentioning
confidence: 99%